2021
DOI: 10.1186/s13256-020-02575-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute gastric dilatation in a patient with severe anorexia nervosa: a case report

Abstract: Background Acute gastric dilatation (AGD) leading to gastric necrosis and perforation has been reported to be a rare but fatal complication in young patients with eating disorders, particularly anorexia nervosa. Case presentation We report a case of a Canadian female patient presenting with mild abdominal pain, with a history of anorexia nervosa, the binge/purge subtype, who was found to have severe acute gastric dilatation on subsequent computed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…However, the association between increased gastric dimensions and gastrointestinal (GI) symptoms, as well as risk for gastric necrosis and perforation, remain to be determined. Pitre et al (2021) reported a gastric dimension of 17 × 18 × 24 cm (~4 L) on CT scan of a patient with severe AN without evidence of necrosis on upper endoscopy. Tweed‐Kent et al (2010) described a stomach measuring 32 × 17.9 cm on CT scan in a patient with AN‐BP, and with evidence of gastric necrosis on laparotomy along with nearly 2 gallons of intragastric material.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the association between increased gastric dimensions and gastrointestinal (GI) symptoms, as well as risk for gastric necrosis and perforation, remain to be determined. Pitre et al (2021) reported a gastric dimension of 17 × 18 × 24 cm (~4 L) on CT scan of a patient with severe AN without evidence of necrosis on upper endoscopy. Tweed‐Kent et al (2010) described a stomach measuring 32 × 17.9 cm on CT scan in a patient with AN‐BP, and with evidence of gastric necrosis on laparotomy along with nearly 2 gallons of intragastric material.…”
Section: Discussionmentioning
confidence: 99%
“…Among individuals with eating disorders (EDs), this condition has only been described on the basis of presumed acute etiology (i.e., acute gastric dilatation), clinically presenting with acute onset epigastric or left upper quadrant abdominal pain along with nausea, vomiting, and frequently abdominal distension. Proposed etiologies for the development of acute gastric dilatation, in those with restrictive EDs, have included: mechanical obstruction due to superior mesenteric artery (SMA) syndrome (Mascolo et al, 2015); following consumption of a large binge (Gyurkovics et al, 2006); in the setting of electrolyte disturbances (Panyko et al, 2020); secondary to gastroparesis, or slowed gastric emptying (Pitre et al, 2021); and secondary to gastric atonicity with distension developing upon resumption of food intake (Vettoretto et al, 2010). However, baseline gastric dimensions in malnourished individuals, secondary to restrictive EDs, have never been examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published cases suggest that massive gastric dilatation may require first-line surgical intervention to address or prevent complications such as perforation, peritonitis, shock, and death [4,5]. In contrast, other case reports with uncomplicated acute gastric dilatation showed that placement of a nasogastric tube alone for decompression could also be an effective treatment [7,8,9]. However, one case report was published about a fatal course of acute gastric dilatation that went unnoticed but was subsequently confirmed by autopsy [6].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Symptoms are unremarkable and include nausea, vomiting, pain and abdominal distension. CT scan can reveal a dilated stomach and eliminate a complication [66]. Prompt nasogastric aspiration can prevent gastric ischemia and perforation with peritonitis.…”
Section: Acute Gastric Distensionmentioning
confidence: 99%